Changes in the Worldview Paradigm of Post-War Education - Коломієць, Тарас Вікторович (Київський національний університет імені Тараса Шевченка, 2025)
The article addresses the issue of changes in the worldview paradigm of post-war education. The new worldview paradigm of post-war education is analyzed, which is based on the provisions of humanistic and post-non-classical science, where the key role is played by the subject-subject (anthropological), creative-integration, synergistic approaches, a human-centric philosophical and educational concept that has a deep value-spiritual content, contributes to the development of a thinking-deliberative type of cognition and is closely correlated with the problem of the national idea.The content of the concepts of «paradigm», «educational paradigm», «humanistic paradigm», «post-non-classical paradigm» is revealed. It is emphasized that education should be aimed not only at reproducing the workforce, even when it comes to specialists focused on fundamental science and the development of innovative technologies, but also at developing the spirituality of the individual, which is based on the highest universal moral qualities and national culture.The role of the teacher as a driving force of innovative activity in education, with a developed adaptive and innovative potential, capable of renewal, open to new ideas and inclined to solve educational problems in an unconventional way, ready to use a variety of educational tools and aimed at achieving competitive advantages, is emphasized.It is proven that it is innovative and humanistic education that will be able to provide a worthy response to the key challenges of post-war reconstruction associated with the shortage of human capital, material resources and time constraints.

У статті актуалізується питання зміни світоглядної парадигми післявоєнної освіти. Проаналізовано нову світоглядну парадигму післявоєнної освіти, що ґрунтується на положеннях гуманістичної й постнекласичної науки, де ключову роль відіграють суб’єкт-суб’єктний (антропологічний), креативно-інтеграційний, синергетичний підходи, людиноцентрична філософсько-освітня концепція, що має глибокий ціннісно-духовний зміст, сприяє розвитку мисленнєво-розмірковуючого типу пізнання й тісно корельована із проблемою національної ідеї. Розкрито зміст понять «парадигма», «освітня парадигма», «гуманістична парадигма», «постнекласична парадигма». Зазначено, що освіта має бути спрямованою не лише на відтворення робочої сили, навіть якщо йдеться про фахівців, орієнтованих на фундаментальну науку й розробку інноваційних технологій, але й на розвиток духовності особистості, яка ґрунтується на вищих загальнолюдських моральних якостях та національній культурі.Обґрунтовано роль педагога як рушійної сили інноваційної діяльності в освіті, з розвиненим адаптаційним та інноваційним потенціалом, здатного до оновлення, відкритого до нових ідей та схильного нетрадиційним способом вирішувати освітні проблеми, готового використовувати різноманітні освітні інструменти й націлені на досягнення конкурентних переваг.Доведено, що саме інноваційна й гуманістична освіта буде здатна дати гідну відповідь на ключові виклики повоєнної відбудови, пов’язані з дефіцитом людського капіталу, матеріальних ресурсів та часовими обмеженнями.
Зміни світоглядної парадигми післявоєнної освіти
Keywords: education; paradigm; innovation; culture; science; teacher; humanocentrism; humanism; освіта; парадигма; інновація; культура; наука; педагог; людиноцентризм; гуманізм